2021
DOI: 10.3390/ijms22031260
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Apolipoprotein D in Cuprizone-Induced Cell Line Models: A Potential Therapeutic Approach for Multiple Sclerosis and Demyelinating Diseases

Abstract: Apolipoprotein D (Apo D) overexpression is a general finding across neurodegenerative conditions so the role of this apolipoprotein in various neuropathologies such as multiple sclerosis (MS) has aroused a great interest in last years. However, its mode of action, as a promising compound for the development of neuroprotective drugs, is unknown. The aim of this work was to address the potential of Apo D to prevent the action of cuprizone (CPZ), a toxin widely used for developing MS models, in oligodendroglial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Reference Collection 19 (Do Carmo et al, 2007;Ganfornina et al, 2008;Nowicki et al, 2009;Sasaki et al, 2009;Bajo-Grañeras et al, 2011aMartínez et al, 2013;Dassati et al, 2020;Diez-Hermano et al, 2020;Martínez-Pinilla et al, 2021). Reference Collection 20 (Blais et al, 1994(Blais et al, , 1995Gillen et al, 1995;Hardardóttir et al, 1997;Ong et al, 1997;Montpied et al, 1999;Trieu and Uckun, 2000;Kim et al, 2001;Leung et al, 2004;Del Signore et al, 2006;Do Carmo et al, 2007Rickhag et al, 2008;Qin et al, 2010;Chia et al, 2011;Puntambekar et al, 2011;García-Mateo et al, 2014;Najyb et al, 2017;Scalf et al, 2019;Schlotter et al, 2020).…”
Section: Apod Systematic Review Reference Collectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference Collection 19 (Do Carmo et al, 2007;Ganfornina et al, 2008;Nowicki et al, 2009;Sasaki et al, 2009;Bajo-Grañeras et al, 2011aMartínez et al, 2013;Dassati et al, 2020;Diez-Hermano et al, 2020;Martínez-Pinilla et al, 2021). Reference Collection 20 (Blais et al, 1994(Blais et al, , 1995Gillen et al, 1995;Hardardóttir et al, 1997;Ong et al, 1997;Montpied et al, 1999;Trieu and Uckun, 2000;Kim et al, 2001;Leung et al, 2004;Del Signore et al, 2006;Do Carmo et al, 2007Rickhag et al, 2008;Qin et al, 2010;Chia et al, 2011;Puntambekar et al, 2011;García-Mateo et al, 2014;Najyb et al, 2017;Scalf et al, 2019;Schlotter et al, 2020).…”
Section: Apod Systematic Review Reference Collectionsmentioning
confidence: 99%
“…Reference Collection 34 (Simard et al, 1990(Simard et al, , 1991(Simard et al, , 1992Blais et al, 1994;Patel et al, 1995;Suresh et al, 1998;Do Carmo et al, 2007;Sreckovic et al, 2013;Cheow et al, 2016;Pamir et al, 2016;Przybycien-Szymanska et al, 2016;Pascua-Maestro et al, 2017, 2018. Reference Collection 35 (Vieira et al, 1995;Sarjeant et al, 2003;Thomas et al, 2003c;Hildebrand et al, 2005;Najyb et al, 2015Najyb et al, , 2017Pascua-Maestro et al, 2017, 2018Martínez-Pinilla et al, 2021). Reference Collection 36 (Sarjeant et al, 2003;Pajaniappan et al, 2011;Tsukamoto et al, 2013;Lai et al, 2017).…”
Section: Apod Systematic Review Reference Collectionsmentioning
confidence: 99%
“…During the last decades, numerous in vitro [51][52][53][54][55] and in vivo [21,[56][57][58][59][60] studies in different neuropathologies such as Alzheimer's disease (AD), Parkinson's disease (PD), or multiple sclerosis (MS) have postulated that Apo D would be part of the cellular defense machinery against oxidative stress and inflammation, with a clear neuroprotective function [21,[61][62][63]. For example, Apo D is upregulated in the CSF, hippocampus, and cerebral cortex of AD patients in correlation with the Braak degeneration stage [64].…”
Section: Apo D In Neurodegenerative Diseasesmentioning
confidence: 99%
“…In an effort to identify the molecules capable of reinforcing the available therapeutic arsenal, a team focused on multiple sclerosis and the evaluation of Apolipoprotein D protection in a cuprizone-induced cell model. The experiments that they carried out showed that the increase in Apolipoprotein D levels, whether exogenous or endogenous, moderately prevents the cytotoxic effects of cuprizone [5].…”
mentioning
confidence: 99%